The Use of Debate Activitiesto Improve Students’ SpeakingAbilityat State Religious Senior High School (MAN 02) of Kepahiang,Bengkulu, Indonesia - Dedi Efrizal (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
This study was carried out to improve the students’ speakingabilitythrough Debate Activitiesin Second Year Students of State Religious Senior High School (MAN 02) of Kepahiangin academis year 2015-2016. The subjects of this study were consisted of 30 students.The method used in this study was Classroom Action Research ( CAR). The Clasroom Action Research design applied in this study was a collaborative classroom action research. It mean that the researcher collaborated with the English teacher of State Religious Senior High School (MAN 02) of Kepahiangas an observer and collaborator. The study was carried out in three cycles. Each cycles consisted of three meetings. The data were gathered in this study through field notes, and test.The result of the study showed that there was improvement of students’ speakingability. Most of the students gradually gained good scores at the end of each cycles. The score of Minimum Mastery Criterion- Kriteria Ketuntasan Minimal (KKM) of English subject was 70 (seventy). The data shows that in cycle I, students speaking achievement is 0% (excellent), 10% (good), 17% (average), 40% (poor), 34% (very poor). In cycle II the students’ speaking achievement is 7% (excellent), 20% (good), 40% (average), 20% (poor) and 13% (very poor). In cycle III students’ speaking achievement is 13% (excellent), 20% (good), 54% (average), 13% (poor) and 0% (very poor). In conclusion, Debate Activitiescould solve the students’ problems and improve their speaking ability